Implementation of the Islamic Religious Education Learning Methods Innovation in the New Normal Era - Minhaji Minhaji; Moh. Nawafil; Abd. Muqit (STAI Hubbulwathan Duri, 2022)
This study aims to analyse and describes the implementation of PAI (Islamic religious education) learning method innovation and the procedures of creating innovative learning methods in the new normal era. This study uses a qualitative case study approach. The researcher tries to reveal learning method innovation and the procedures in the unstable era of the COVID-19 pandemic. The researcher conducted interviews, observations, and documentation to obtain information about the themes studied. Data analysis was carried out circularly, starting with data presentation, data reduction, and concluding. The results showed that PAI learning method innovation in the new normal era is running effectively through the integration of various learning methods, consists of three kinds, the first is the home visit method integrated with project-based learning, the second is the online method integrated with blended learning, and the third is the offline method integrated with inquiry learning. Identification, development and evaluation are the three procedures of creating integrated PAI learning method innovation in the new normal era.